2009
DOI: 10.1890/08-1730.1
|View full text |Cite
|
Sign up to set email alerts
|

A global meta‐analysis of soil exchangeable cations, pH, carbon, and nitrogen with afforestation

Abstract: Abstract. Afforestation, the conversion of non-forested lands to forest plantations, can sequester atmospheric carbon dioxide, but the rapid growth and harvesting of biomass may deplete nutrients and degrade soils if managed improperly. The goal of this study is to evaluate how afforestation affects mineral soil quality, including pH, sodium, exchangeable cations, organic carbon, and nitrogen, and to examine the magnitude of these changes regionally where afforestation rates are high. We also examine potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
335
7
8

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 447 publications
(398 citation statements)
references
References 101 publications
26
335
7
8
Order By: Relevance
“…Thus, our analysis assumes that soil C stocks have reached equilibrium values under current land uses. Undoubtedly, other factors not incorporated in our analyses also affect the direction and magnitude of changes in soil C stocks, including site preparation, fertilization and improved management (26), species effects (27), and legacy effects of multiple landuse transitions. However, we did not stratify according to these factors, as their effect is less studied and no georeferenced databases of these factors exist that might be used to improve predictions of soil C stock changes following land-use change.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, our analysis assumes that soil C stocks have reached equilibrium values under current land uses. Undoubtedly, other factors not incorporated in our analyses also affect the direction and magnitude of changes in soil C stocks, including site preparation, fertilization and improved management (26), species effects (27), and legacy effects of multiple landuse transitions. However, we did not stratify according to these factors, as their effect is less studied and no georeferenced databases of these factors exist that might be used to improve predictions of soil C stock changes following land-use change.…”
Section: Discussionmentioning
confidence: 99%
“…Published studies located between 28°3 5′ N and 28°15′ S latitude were identified from previous meta-analyses and reviews (14,27,(32)(33)(34) or from searching online scientific databases. The majority of the studies were conducted between 23°N and 23°S latitudes and only a few are considered subtropical.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism by which woody vegetation boosts C accumulation in soils is poorly known. Berthrong et al (2009) suggested that urban woody vegetation increases the input of organic matter with a high C/N ratio and, since litter with high C/N decomposes more slowly (Stevenson, 1994), the soils will accumulate C stocks over time. Although woody vegetation, compared to lawn, may increase the C/N ratio in urban greenspace soils (Livesley et al, 2016), other urban studies have found no evidence of such an effect (Golubiewski, 2006;Raciti et al, 2011;Edmondson et al, 2014b).…”
Section: General Effects Of Plant Functional Groups On Urban Park Soilsmentioning
confidence: 99%
“…The relative proportion of C and N in the soil can be used as an indicator of soil quality, describing the relative proportion of nitrogen that is either mineralized by soil microbes or immobilized into the microbial biomass (Berthrong et al, 2009). The equal C/N ratio across all studied park soils implies that the availability of N, i.e., soil fertility (Brady and Weil, 2008), is similar beneath the three vegetation types in our study (per age class), despite the 30% higher N concentration under the evergreens than under lawns.…”
Section: General Effects Of Plant Functional Groups On Urban Park Soilsmentioning
confidence: 99%